Effect of Sodium Chloride Concentration on Aeromonas hydrophila, Proximate and Organoleptic Analyses in Catfish (Clarias sp.) Flesh - Dian Wahyu Wardani; Abdul Mulki Purnama; Hartati Kartikaningsih; Abdul Aziz Jaziri (Journal of Aquaculture and Fish Health, 2021)
Intensive aquaculture on catfish (Clarias sp.) has been getting problem due to pathogenic bacteria such as Aeromonas hydrophila. Fish infected by A. hydrophila would bear various symptoms, including hemorrhagic on the skin, gills, ulcers, and pale skin color. To tackle this situation, salt (sodium chloride) treatment with different concentrations can be used, which acts as both bactericidal and bacteriostatic agents. This study aimed to determine the effect of different salt concentration (viz. 0%, 5%, 10% and 15%) added in the treated samples by evaluating the availability of pathogenic bacteria using total plate count (TPC) and total A. hydrophila, along with proximate and organoleptic assessment. An experimental method was used in this research with a completely randomized design (CRD). The results showed that the TPC value in all sample treatments was higher (around 5 × 105) than that recommended by Indonesia National Standard (SNI). On the other hand, the sample added 10% and 15% salts exhibited a significant effect on the decrease of A. hydrophila through a selective medium Rimler-Shotts agar. For proximate analysis, the treated samples contained in the ranges of 67.33-80.03% (WB), 0.91-13.58% (WB), 35.06-69.92% (DW) and 4.41-1451% (DW) of moisture, ash, crude protein, and fat, respectively. In addition, a sensory test of catfish flesh samples showed that all parameter tests, including mucus, odor, and texture met the referred standard. Taken together, this study may contribute to developing an approach in treating pathogenic bacteria during rearing and also post-harvesting catfish; however, further research is required to obtain a better outcome in dealing with food safety issues.